Oxford practice grammar with answers - Eastwood, John (Oxford Univ. Press, 1999)
The book consists of 153 units, each on a grammatical topic. The units cover the main areas of English grammar. Special attention is given to those points which are often a problem for learners: the maining of the different verb forms, the use of the passive, conditionals, prepositions and so on.